Ovarian Sex Hormones Modulate Compulsive, Affective and Cognitive Functions in A Non-Induced Mouse Model of Obsessive-Compulsive Disorder - Mitra, Swarup; Bastos, Cristiane P.; Bates, Katherine; Pereira, Grace S.; Bult-Ito, Abel (Frontiers in Behavioral Neuroscience, 2016)
There is currently a lack of understanding how surgical menopause can influence obsessions, compulsions and associated affective and cognitive functions in female OCD patients. Early menopause in women due to surgical removal of ovaries not only causes dramatic hormonal changes, but also may induce affective and cognitive disorders. Here, we tested if surgical removal of ovaries (ovariectomy, OVX), which mimics surgical menopause in humans, would result in exacerbation of compulsive, affective and cognitive behaviors in mice strains that exhibit a spontaneous compulsive-like phenotype. Female mice from compulsive-like BIG, non-compulsive SMALL and randomly-bred Control strains were subjected to OVX or sham-surgery. After seven days animals were tested for nest building and marble burying to measure compulsive-like behavior. The elevated plus maze and open field tests measured anxiety-like behaviors, while memory was assessed by the novel object recognition. Acute OVX resulted in exacerbation of compulsive-like and anxiety-like behaviors in compulsive-like BIG mice. No significant effects of OVX were observed for the non-compulsive SMALL and Control strains. Object recognition memory was impaired in compulsive-like BIG female mice compared to the Control mice, without an effect of OVX on the BIG mice. We also tested whether 17 β-estradiol (E2) or progesterone (P4) could reverse the effects of OVX. E2, but not P4, attenuated the compulsive-like behaviors in compulsive-like BIG OVX female mice. The actions of the sex steroids on anxiety-like behaviors in OVX females were strain and behavioral test dependent. Altogether, our results indicate that already existing compulsions can be worsened during acute ovarian deprivation concomitant with exacerbation of affective behaviors and responses to hormonal intervention in OVX female mice can be influenced by genetic background.